SOCIO-POLITICAL CONTEXT AND STRATEGY OF MODERN MARKETING - Latinović, Boris (Political Review, 2023)
Consumer needs are characterized by a very distinct complexity. The research on this topic is very interesting from the point of view of the availability of numerous and very different sociopolitical factors that, by their nature, influence the consumer. Also, the consumer, as an individual, has many characteristics that are interesting and very influential on his purchasing decisions, and which are the subject of study, both by retailers and marketing experts, with the purpose of providing better consumption results. All of them make maximum efforts to make the customer satisfied. As a subject of research in the paper, an analysis of consumer behavior was performed, the environmental factors that influence their behavior, as well as the combination of environmental factors that influence the decision to initiate an action, were defined. The aim of the research is to analyze the consumer in the context of the social and sociopolitical dimension, as well as to define the impact of marketing on his behavior. Based on the research, we can conclude that each consumer is an individual for himself, and accordingly expresses and satisfies different wishes and needs. His wants and needs can be systematically influenced through marketing activities. The way in which the consumerism of consumers and their decisions is influenced by the sociopolitical environment and the application of marketing activities is extremely interesting. The modern environment is characterized by the necessity of digital marketing, it represents one of the prerequisites for achieving competitiveness on the market, whether it is a product, service or person.
Keywords: politics; society; consumers; environment; marketing